Assessment of basal TSPO expression and [18F]DPA-714 biodistribution in healthy mice and post-ischemic brain using PET imaging - Brígida Gomes de Almeida Schirmer; Juliana de Oliveira Silva; Douglas Boniek Silva Navarro; João Vitor Reis Marques; Mariana Duarte de Souza; Ianara Pereira Silva; Juliana Batista da Silva; Carlos Malamut (Brazilian Journal of Radiation Sciences, 2025)
Positron emission tomography (PET) is an important tool in preclinical studies in small animals, providing real-time insights into biochemical, metabolic, physiological, and functional processes. PET imaging also enables the assessment of biological responses and biodistribution of novel radiolabeled compounds within a single animal, minimizing the need for larger animal groups. In particular, PET imaging with [18F]DPA-714, a Translocator Protein (TSPO) ligand, has shown high predictive and prognostic value in diseases associated with neuroinflammation and correlates well with functional outcomes. In this study, basal expression of TSPO was investigated in vivo in C57BL/6 mice and PET was proposed as a method to track biodistribution of new molecules. Male C57BL/6 mice aged 6–9 weeks and weighing 20–30 g were divided into healthy and ischemic groups. The ischemic group was subjected to transient global cerebral ischemia induced by 25 min of bilateral common carotid artery occlusion (BCCAO) followed by reperfusion. Baseline imaging of [18F]DPA-714 biodistribution was performed in healthy mice with static whole-body scans at 0-20, 20-40, 40-60, and 60-80 min post-injection intervals. After ischemia, PET scans were used to examine the cerebral uptake of [18F]DPA-714. The results confirm that PET is an effective, non-invasive technique for biodistribution studies. Analysis of SUVmean, SUVmax, and SUVpeak metrics showed increased sensitivity for increased uptake in the brain following ischemia, highlighting its importance in preclinical neuroinflammation models. Furthermore, baseline uptake of [18F]DPA-714 was observed in multiple organs, reflecting the baseline expression of TSPO and its metabolic and clearance pathways. The comparable baseline uptake observed in the brain and muscle underscores its potential as a reliable marker for studying TSPO-related inflammatory processes.